A kind of highly wear-resistant and waterproof cycling heated gloves

By using surface-modified polyester fabric and dandelion-shaped alumina-modified composite rubber in electric heating gloves, the problem of insufficient wear and waterproof performance of existing gloves is solved, achieving higher wear, waterproof and anti-slip performance, and improving riding safety and comfort.

CN118787159BActive Publication Date: 2025-03-14SHENZHEN EIGDAY HEATING LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411145317.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-03-14
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

Existing electric heating gloves have shortcomings in wear resistance and waterproof performance, which is difficult to meet the market demand for high-performance riding gloves.

Method used

Surface modified polyester fabric is used as the waterproof and wear-resistant outer layer, and combined with dandelion-shaped alumina modified composite rubber as the wear-resistant and anti-slip layer, the waterproof and wear-resistant performance of the gloves are improved through the synergy of the multi-layer structure and materials.

Benefits of technology

It significantly improves the wear resistance, waterproof, anti-slip and comprehensive performance of gloves, extends the service life, and improves the comfort and safety of riding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118787159B_ABST
    Figure CN118787159B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electric heating gloves, a highly wear-resistant and waterproof cycling heating glove, comprising a glove body, wherein the glove body is sequentially composed of a waterproof and wear-resistant outer layer, a heat-insulating layer, a heating layer and an inner layer from the outside to the inside; the heating layer is distributed in the form of strips inside the back of the hand of the glove body; a wear-resistant and shock-absorbing rubber pad is provided at the palm of the outer surface of the glove body; a wear-resistant and anti-skid layer is provided on the front of the fingers of the outer surface of the glove body; the wear-resistant and shock-absorbing rubber pad and the wear-resistant and anti-skid layer are both adhered to the outer surface of the glove body by epoxy resin; the surface of the wear-resistant and shock-absorbing rubber pad and the surface of the wear-resistant and anti-skid layer are both provided with wear-resistant and anti-skid convex points; a battery bag, a zipper, a storage battery, a temperature control module, etc. are provided on the back of the hand of the back of the glove body. The present invention realizes waterproof, wear-resistant and self-cleaning by treating the outer layer of the polyester fabric with fluorine-free sol, and combines the dandelion-shaped alumina-modified composite rubber wear-resistant and anti-skid layer and the wear-resistant and anti-skid convex point design to comprehensively improve the waterproof, wear-resistant, anti-skid and comprehensive performance of the gloves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electric heating gloves, in particular to a highly wear-resistant and waterproof cycling heating glove. Background Art

[0002] In the field of outdoor cycling, as exploring the limits and enjoying nature have become new trends, the performance requirements for equipment are becoming increasingly stringent. Although traditional cycling gloves can provide basic protection, their wear resistance and waterproof performance are gradually becoming insufficient in bad weather, such as rain and snow or long journeys. Therefore, it is particularly important to develop highly wear-resistant and waterproof cycling heated gloves. These gloves can not only effectively resist rain penetration and keep hands dry and comfortable, but their excellent wear resistance can also reduce wear and extend service life under complex road conditions. At the same time, the built-in heating system can also provide warmth in cold weather, ensuring that the rider's hands are flexible and free, without fear of severe cold challenges, greatly improving the riding experience and safety.

[0003] At present, the electric heating layer of heating gloves has made a lot of progress, but there are still some shortcomings. (1) The wear resistance still needs to be further improved to meet the requirements of more demanding use environments. For example, during riding on rugged mountain roads, gravel roads, or frequent contact with rough objects, the wear resistance of gloves is directly related to their service life and safety. For example, the Chinese patent with publication number CN216909127U discloses a ski glove with heating function. The glove is based on an outer layer made of breathable and waterproof fabric, but the outer layer is not designed for wear resistance, so the wear resistance needs to be improved. (2) Waterproofness is still one of the technical difficulties. For example, the Chinese patent with publication number CN212212820U discloses an aerogel electric heating glove. The outer layer is made of microfiber synthetic leather. The microfiber synthetic leather outer layer itself has a certain degree of waterproofness, but the waterproof effect is limited. It is difficult to achieve the requirement of complete waterproofness. It also needs to be improved and optimized by combining product design and secondary processing methods. In order to make up for the shortcomings of current technology, it is urgent to develop a new type of heated gloves, whose wear resistance and waterproof performance must be significantly improved to meet the market demand for high-performance cycling gloves. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a highly wear-resistant and waterproof cycling heated glove to solve the problem that the current electric heating gloves have insufficient performance in terms of wear resistance and waterproofness.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A highly wear-resistant and waterproof cycling heated glove, comprising a glove body, wherein the glove body is composed of a waterproof and wear-resistant outer layer, a heat-insulating layer, a heating layer and an inner layer from the outside to the inside; the waterproof and wear-resistant outer layer, the heat-insulating layer, the heating layer and the inner layer are connected together by stitches, and each layer is bonded by a polyurethane adhesive; the heating layer is distributed in the form of strips on the back of the hand of the glove body; a wear-resistant and shock-absorbing rubber pad is provided on the palm of the glove body; a wear-resistant and anti-skid layer is provided on the front of the fingers of the glove body; the wear-resistant and shock-absorbing rubber pad and The wear-resistant and anti-skid layers are adhered to the surface of the glove body by epoxy resin; the surface of the wear-resistant and shock-absorbing rubber pad and the surface of the wear-resistant and anti-skid layer are provided with wear-resistant and anti-skid protrusions; a battery bag is provided on the back of the hand on the back of the glove body; the battery bag is made of elastic waterproof fabric; the battery bag is provided with a zipper; the battery bag has a built-in battery, and the battery is a rechargeable battery; a temperature control module is also provided on the back of the hand on the back of the glove body; the temperature control module is provided with a switch and a temperature control knob; the battery and the heating layer are respectively connected to the temperature control module through wires.

[0009] Furthermore, the waterproof and wear-resistant outer layer is a surface-modified polyester fabric, and its preparation method is: an impregnation-compression-curing process, firstly, the polyester fabric is completely immersed in the fluorine-free sol, the impregnation time is 5 to 10 minutes, and then the polyester fabric is pressed between two rollers of an automatic filling machine, and the pressing pressure is 2 to 3 kg / cm 2 After the sheeting treatment, a curing treatment is performed. The curing treatment parameters are: drying at 75-85°C for 10-20 minutes, then putting it into a 125-135°C oven for curing for 5-10 minutes, and then repeating the impregnation-sheeting-curing process three times to finally obtain a surface-modified polyester fabric.

[0010] Furthermore, the preparation method of the fluorine-free sol is as follows: after uniformly mixing 10 to 18 parts of hexadecyltrimethoxysilane, 12 to 20 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 30 to 50 parts of ethanol by weight, 6 to 12 parts of hydrochloric acid and 4 to 8 parts of 1-methylimidazole are simultaneously added dropwise thereto, and then stirred at room temperature for 20 to 30 hours to finally obtain the fluorine-free sol.

[0011] Furthermore, the polyester fabric is woven from polyester fibers, the densities of the polyester fiber warp and polyester fiber weft are 55-65 strands / cm and 70-85 strands / cm respectively, the polyester fiber is 4.5-5.5 g / km, and the density of the polyester fabric is 60-68 g / m 2 , the thickness of polyester fabric is 1 to 2 mm.

[0012] The present invention uses surface-modified polyester fabric as the waterproof and wear-resistant outer layer of gloves for the following multiple purposes: 1. From the hydrophobic aspect, the present invention uses a fluorine-free sol to treat the polyester fabric, replacing the traditional fluorine-containing compound reagent. This new sol is based on the hydrolysis and condensation process of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, so that the surface of the fabric forms super-hydrophobicity, thereby achieving an excellent hydrophobic effect. 2. In terms of self-cleaning, this treatment method enables the coated polyester textile to exhibit self-cleaning properties, which helps to reduce moisture adsorption and keep the surface of the fabric clean, thereby extending the service life. In addition, the method can also enable the polyester fabric to maintain most of its hydrophobic properties after a long wear cycle, indicating that it has good durability and self-healing ability. 3. In terms of wear resistance, the surface-modified polyester fabric obtains a more wear-resistant outer layer through multiple impregnation-compression-curing process treatments. This treatment method not only improves the hydrophobicity and self-cleaning properties of the fabric, but also increases its durability, so that it can better resist wear during use and extend its service life. Therefore, the design aims to comprehensively improve the performance of polyester fabrics, achieve multiple functions such as hydrophobicity, self-cleaning, and wear resistance, and provide a new idea and solution for the research and development of sustainable hydrophobic and fluorine-free textile coatings.

[0013] The present invention aims to significantly improve the waterproof and wear-resistant properties of polyester fabrics by finely regulating multiple key parameters in the design and manufacture of polyester fabrics. Specifically, the comprehensive optimization of these parameters ensures that the fabric can not only effectively resist water penetration, but also maintain the integrity and durability of the structure in a high-wear environment. First, the density of the warp and weft of the polyester fiber is precisely set within the range of 55-65 / cm ​​and 70-85 / cm. A higher fiber density means that the fibers are more closely interwoven per unit area, reducing the channels for water penetration, thereby enhancing the waterproof performance of the fabric. At the same time, the tight fiber structure also improves the smoothness of the fabric surface, reduces the wear points caused by friction, and indirectly enhances the wear resistance. Secondly, the linear density of the polyester fiber is set to 4.5-5.5g / km, and the selection of this range takes into account the strength and flexibility of the fiber. Coarser fibers can provide better physical support and enhance the wear resistance of the fabric without excessively sacrificing its softness and comfort. In addition, the appropriate fiber linear density also helps to form a more uniform and dense fabric structure, further improving the waterproof effect. Furthermore, the density of polyester fabric is controlled at 60-68g / m 2Between. A higher fabric density not only increases the total amount of fibers per unit area, improves the overall strength and wear resistance of the fabric, but also makes the fabric surface more compact, reducing the possibility of water penetration. This density setting is the key to improving waterproof and wear resistance. Finally, the thickness of the polyester fabric is set to 1 to 2 mm. The selection of this range not only ensures the lightness of the fabric, but also provides it with sufficient thickness to resist wear. Appropriate thickness can increase the air layer inside the fabric, improve the warmth retention performance, and also enhance the tear and wear resistance of the fabric to a certain extent. In addition, the thicker fabric structure can better accommodate waterproof coatings or treatment agents, further improving the waterproof effect. In summary, the present invention achieves a significant improvement in the waterproof and wear resistance of polyester fabrics by finely regulating key parameters such as the warp and weft density, line density, fabric density and thickness of polyester fibers. The optimization of these parameters not only meets the high requirements for fabric performance in specific application scenarios, but also ensures that the fabric has good comfort and durability while maintaining excellent performance.

[0014] Furthermore, the wear-resistant and anti-skid layer is a dandelion-shaped alumina-modified composite rubber, and its preparation method is as follows: by weight, 10 to 16 parts of natural rubber and 9 to 18 parts of EPDM rubber are added to a double-roll mill, heated to 30 to 40°C, crushed and softened for 8 to 16 minutes, then 3 to 8 parts of surface-modified dandelion-shaped alumina nanoparticles, 2 to 5 parts of maleic anhydride-grafted EPDM rubber and 2 to 4 parts of stearic acid are added, heated to 45 to 55°C, mixed at 60 to 80 rpm for 10 to 18 minutes, then 2 to 6 parts of sulfur are added, and mixing is continued for 5 to 10 minutes. Finally, the mixed colloid is taken out and made into a sheet using a double-roll mill, and then it is vulcanized at 150 to 165°C and 25 to 35 MPa for 5 to 9 minutes. After the vulcanization is completed, the vulcanized sheet is immediately taken out from the mold and quickly cooled under running water.

[0015] Furthermore, the preparation method of the surface modified dandelion-shaped aluminum oxide nanoparticles is as follows: by weight, 15 to 25 parts of dandelion-shaped aluminum oxide nanoparticles are added to 80 to 100 parts of toluene and ultrasonically dispersed for 20 to 45 minutes, and then 3 to 7 parts of (3-aminopropyl) triethoxysilane are added and stirred at 75 to 85°C for 20 to 35 hours. After cooling, the filter is filtered and the filter residue is washed three times with toluene. The toluene needs to completely submerge the filter residue during each washing process. After washing, the filter residue is placed in a vacuum drying oven at room temperature and dried for 24 to 36 hours to obtain surface modified dandelion-shaped aluminum oxide nanoparticles.

[0016] Furthermore, the preparation method of the dandelion-shaped alumina nanoparticles is as follows: in parts by weight, 6 to 15 parts of aluminum nitrate, 10 to 18 parts of ammonium sulfate and 100 parts of deionized water are mixed evenly, and then dripped dropwise into 200 parts of ammonium bicarbonate solution with a concentration of 1.5 mol / L. During the dripping process, it is necessary to stir evenly at a speed of 100 to 160 rpm, and then after standing for 10 to 20 hours, a precursor gel is obtained by filtering, and then the precursor gel is washed three times with deionized water, and each washing needs to completely submerge the precursor gel with deionized water. After washing, it is dried in an oven until complete, and then placed in a muffle furnace for calcination to obtain dandelion-shaped alumina nanoparticles, wherein the calcination process parameters are: in an air atmosphere, the calcination temperature is 1100 to 1250°C, and the calcination time is 2 to 4 hours.

[0017] The present invention adopts dandelion-shaped alumina-modified composite rubber as the waterproof and wear-resistant outer layer of the gloves, aiming to achieve significant improvement in multiple key performances of the gloves through a series of carefully designed chemical and physical modification processes. The specific design purposes are as follows: First, dandelion-shaped alumina nanoparticles are cleverly integrated into the composite rubber by virtue of their unique morphology and surface characteristics, greatly enhancing the wear resistance of the gloves. These nanoparticles are evenly distributed in the rubber matrix, building a solid support network, effectively resisting the invasion of external wear factors such as friction, cutting, etc., thereby significantly extending the service life of the gloves. Secondly, with the help of maleic anhydride grafting technology, strong chemical bonding is achieved between EPDM rubber and the rubber matrix, significantly improving the flexibility and elasticity of the gloves. This grafting modification not only strengthens the interaction between rubber molecular chains, but also gives the rubber excellent deformation recovery ability and tear resistance while maintaining high strength, providing the wearer with a more comfortable and flexible wearing experience. In terms of waterproof performance, the dense structure and excellent chemical stability of the composite rubber itself work together to further enhance the waterproof function of the gloves, ensuring that the inside of the gloves can remain dry and comfortable even in humid or underwater environments. The improvement in anti-slip performance is attributed to the synergistic effect of the microscopic rough surface of the dandelion-shaped aluminum oxide nanoparticles in the rubber matrix and the high friction coefficient of the rubber itself. This design allows the gloves to generate sufficient friction when contacting various surfaces, and maintain a stable grip even in a wet or greasy working environment, greatly reducing the risk of slipping. Finally, from the perspective of mechanical properties, the dandelion-shaped alumina-modified composite rubber gloves exhibit excellent comprehensive mechanical properties while maintaining their lightweight characteristics. The material performs well in a variety of mechanical tests such as tension, compression, and bending, and can withstand large external loads without being easily damaged, providing the wearer with solid and reliable hand protection. In summary, the present invention adopts dandelion-shaped alumina-modified composite rubber as the waterproof and wear-resistant outer layer of the gloves. By comprehensively optimizing the performance and deeply exploring the mechanism, the gloves are significantly improved in terms of wear resistance, flexibility, waterproofness, anti-slip and mechanical properties, providing an efficient, safe and comfortable innovative solution for the field of modern industry and personal protection.

[0018] Furthermore, the preparation method of the wear-resistant and anti-skid bumps is as follows: by weight, 3 to 8 parts of natural latex, 30 to 45 parts of nitrile rubber latex, 5 to 8 parts of dumbbell-shaped nano silicon carbide ceramic particles, 2 to 6 parts of EPDM elastomer powder, 1 to 3 parts of silane coupling agent KH-550 and 2 to 4 parts of sulfur are mixed evenly, and then coated on the wear-resistant and anti-skid layer in a dot coating manner, and then vulcanization treatment is performed. The parameters of the vulcanization treatment are: first, keep warm at 45 to 60°C for 30 to 40 minutes, then heat to 85 to 100°C and keep warm for 30 to 45 minutes, and cool after vulcanization is completed.

[0019] Furthermore, the preparation method of the dumbbell-shaped nano-silicon carbide particles is as follows: by weight, 20 to 35 parts of silicon dioxide, 20 to 30 parts of sucrose and 2 to 5 parts of ferrocene are mixed evenly by high-energy ball milling to obtain a nano-scale precursor, which is then heated to 1200 to 1400° C. at a heating rate of 5 to 10° C. / min in a tubular furnace in an argon atmosphere, kept warm for 2 to 4 hours, and cooled to obtain dumbbell-shaped nano-silicon carbide particles.

[0020] Furthermore, the dumbbell-shaped nano-silicon carbide particles have an average length of 100 to 200 nm and a diameter of 45 to 85 nm.

[0021] Furthermore, the wear-resistant and anti-skid convex points are spherical and evenly distributed on the wear-resistant and anti-skid layer. The diameter of the wear-resistant and anti-skid convex points is 1.0-2.0 mm; the height is 0.5-1.5 mm, and the distribution density is 10-25 / cm 2 .

[0022] The wear-resistant and anti-skid convex point design of the present invention cleverly combines multiple materials and technical advantages, aiming to significantly improve the anti-skid and wear-resistant properties of the material. Its unique preparation method uses a precise ratio of natural latex, nitrile rubber emulsion, dumbbell-shaped nano silicon carbide ceramic particles, EPDM elastomer powder, silane coupling agent KH-550 and sulfur, and uses a point coating technology to evenly apply these high-performance ingredients on the surface of the wear-resistant and anti-skid layer. Subsequently, a carefully designed vulcanization process, including two stages of low-temperature insulation and high-temperature insulation, ensures the firm combination of the convex point material and the full play of its excellent performance. It is particularly worth mentioning that the dumbbell-shaped nano silicon carbide particles used, the preparation method of which innovatively combines high-energy ball milling and high-temperature carbonization technology, ensures the uniformity of the particles at the nanoscale and the formation of a specific morphology. These particles not only have precise control of average length and diameter, but also enhance the interfacial bonding force with the matrix material with their unique dumbbell-shaped structure, thereby effectively improving the overall performance of the wear-resistant and anti-skid convex points. The wear-resistant and anti-skid convex points finally formed are evenly distributed on the waterproof and wear-resistant layer and the wear-resistant and shock-absorbing rubber pad in a spherical shape. The appropriate diameter, height and distribution density design not only ensures sufficient anti-skid effect, but also takes into account the comfort and aesthetics of wearing. This series of careful designs make the wear-resistant and anti-skid convex points of the present invention have a wide range of application prospects in many fields such as industry, sports, and outdoor activities, providing users with a safer and more reliable protection solution.

[0023] In deepening the design of the present invention, the parameters of the wear-resistant and anti-skid convex points are carefully set, aiming to significantly improve its waterproof and wear-resistant properties while maintaining excellent anti-skid effects. Specifically, these spherical convex points are evenly inlaid on the surface of the wear-resistant and anti-skid layer, and a perfect combination of functionality and durability is achieved through a series of precisely controlled parameters. First, the diameter of the wear-resistant and anti-skid convex points is set to 1.0-2.0 mm. The selection of this range takes into account both the demand for anti-skid effects and the improvement of wear resistance. A smaller diameter helps to increase the number of convex points per unit area, thereby improving the overall anti-skid performance, especially in slippery environments, where dense convex points can effectively increase the friction between the sole or walking surface and reduce the risk of slipping. At the same time, the appropriate diameter range can also ensure that the convex points can maintain a certain structural stability when worn, extending their service life. Secondly, the height of the convex points is designed to be 0.5-1.5 mm, which not only provides sufficient support and feedback for walking, but also optimizes the waterproof performance. When rain or liquid splashes, the height of the bumps can form tiny drainage channels, promote the rapid flow of water, and reduce the residence time of the liquid on the surface, thereby keeping the surface of the anti-slip layer dry and clean. In addition, the appropriate height can also enhance the ability of the bumps to resist external impact and wear, so that they can still maintain a stable shape when facing heavy objects or frequent trampling, and are not easily deformed or damaged. Finally, the distribution density is set to 10 to 25 / cm 2 , this range is based on comprehensive consideration of anti-skid, wear resistance and visual aesthetics. A lower distribution density may not provide sufficient anti-skid effect, while too high a density may increase the difficulty of cleaning and affect walking comfort. Within this range, the convex points can be evenly and moderately distributed on the anti-skid layer, which not only ensures the balance of anti-skid performance, but also avoids walking discomfort and cleaning problems caused by excessive density. At the same time, the appropriate distribution density also helps to improve the overall wear resistance of the anti-skid layer, because the dispersed convex points can more effectively disperse and resist external wear forces, extending the service life of the anti-skid layer. In summary, the present invention achieves a significant improvement in waterproof, wear-resistant and anti-skid performance by accurately setting key parameters such as the diameter, height and distribution density of wear-resistant and anti-skid convex points. These parameters cooperate with each other to form an efficient, durable and comfortable anti-skid solution.

[0024] Furthermore, the heat insulation layer is 3M Thinsulate fx type thermal insulation material.

[0025] The present invention uses 3M Thinsulate fx thermal insulation material as the thermal insulation layer of the gloves, mainly based on its excellent adaptability and durability. The material achieves significant stretchability in all directions through a unique combination of elastic polyolefin microfibers and staple fibers, and can maintain a stable thermal insulation effect even during the stretching and bending movements during the wearing of the gloves, avoiding the problem of breakage of traditional thermal insulation materials due to extreme conditions. In addition, its good shape recovery ability ensures that the gloves are not easy to wrinkle during use, thereby maintaining the overall appearance and user experience. In summary, Thinsulate fx thermal insulation material provides a reliable thermal insulation layer for gloves, demonstrating its advantages in practical applications.

[0026] Furthermore, the heating layer is a self-limiting temperature electric heating film.

[0027] The self-limiting temperature electric heating film in the present invention uses pure cotton material as a stable matrix and cleverly integrates composite polymer materials as the core heating medium. This electric heating film has a unique design, and the heat it generates is mainly efficiently transmitted in the form of far-infrared radiation, and the radiation wavelength is precisely controlled, ensuring the pertinence and efficiency of energy transfer. What is particularly outstanding is that the electric heating film has a self-limiting temperature characteristic, can intelligently adjust the temperature, effectively avoids local overheating, and improves the safety and comfort of use. In terms of physical properties, the electric heating film exhibits excellent quality: its flexible design gives it good anti-bending ability, ensuring that it can still work stably under various bending conditions; the temperature distribution is uniform, avoiding the generation of hot spots; the electrodes are firmly connected, the performance is stable under working conditions, and the power attenuation is minimal after long-term use, which significantly extends the service life of the gloves.

[0028] Furthermore, the inner layer is made of Coolmax fiber knitted fabric.

[0029] The selection of Coolmax fiber knitted fabric as the inner layer of the heating gloves in the present invention shows a series of significant advantages and characteristics. Its unique fiber structure ensures efficient hygroscopicity and breathability, and can effectively manage the fine moisture generated by the hands even in the warm environment of the heating gloves, avoiding the discomfort caused by sweat accumulation. This performance not only improves the wearing comfort of the gloves, but also promotes air circulation, helps to maintain a dry environment inside the gloves, and keeps the hands dry and comfortable even when worn for a long time in cold weather. In addition, the four-groove design of the Coolmax fiber knitted fabric optimizes the transmission path of moisture, can quickly guide the trace sweat generated by the hands to the outer layer of the gloves, reduce the damp and cold feeling, and enhance the warming effect. This feature complements the heating function and provides more comprehensive protection for the hands, whether it is outdoor adventure, skiing or daily commuting, it can ensure that the hands are warm and dry. In addition, the four-groove design of the Coolmax fiber knitted fabric optimizes the transmission path of moisture, can quickly guide the trace sweat generated by the hands to the outer layer of the gloves, reduce the damp and cold feeling, and enhance the warming effect. This feature complements the heating function and provides more comprehensive protection for the hands, ensuring that the hands are warm and dry whether for outdoor adventures, skiing or daily commuting. At the same time, Coolmax fiber knitted fabric also has good durability and antibacterial properties, which can resist daily wear and tear, extend the service life of the gloves, and inhibit bacterial growth to maintain the cleanliness and health of the hands, reducing the odor problem that may be caused by wearing gloves for a long time. Overall, Coolmax fiber knitted fabric, as the inner layer of heated gloves, brings users a better wearing experience with its excellent moisture absorption and breathability, warmth and comfort, antibacterial and durability.

[0030] The highly wear-resistant and waterproof cycling heating gloves designed in this scheme are arranged in sequence from the outside to the inside with a waterproof and wear-resistant outer layer, a heat-insulating layer, a heating layer and an inner layer. Through the double reinforcement of stitching and polyurethane adhesive, the overall firmness and sealing of the gloves are ensured, and they can effectively resist the invasion of external wind and rain and daily wear and tear. The combination of the waterproof and wear-resistant outer layer with the wear-resistant shock-absorbing rubber pad and the wear-resistant and anti-slip layer, as well as the wear-resistant and anti-slip bumps evenly distributed on the surface, significantly improves the wear resistance and grip stability of the gloves, ensuring riding safety. At the same time, the battery bag design of the elastic waterproof fabric is convenient for the replacement and charging of the battery, and ensures the waterproof effect of the back of the gloves, improving the convenience and safety of use. The heating layer is distributed in the form of strips on the inside of the back of the hand. Compared with full coverage, this design not only saves energy, but also accurately heats the areas of the hand that are most susceptible to cold, improving energy utilization efficiency. The addition of the temperature control module enables users to freely adjust the temperature of the gloves according to actual needs through the setting of the switch and the temperature control knob, achieving a personalized and comfortable experience. In addition, the epoxy resin bonding technology of the wear-resistant and anti-skid layer and the wear-resistant and shock-absorbing rubber pad not only enhances the bonding strength between the components and the glove body, but also further improves the durability and protective performance of the gloves, reflecting the innovative application of technology. In summary, this solution has created a pair of cycling gloves that are highly wear-resistant, waterproof, heated, and comfortable through scientific and reasonable structural design and innovative and practical functional integration, meeting the diverse needs of cycling enthusiasts.

[0031] (3) Beneficial technical effects

[0032] 1. In the waterproof and wear-resistant outer layer, the present invention innovatively uses fluorine-free sol to treat polyester fabric, aiming to create a glove outer layer that is waterproof, self-cleaning and wear-resistant. The sol is based on the hydrolysis and condensation of specific silanes, which gives the fabric super-hydrophobicity, achieves efficient waterproofing and reduces moisture adsorption, extending the service life. At the same time, its self-cleaning properties and durability are remarkable, and the wear resistance is enhanced through multiple process treatments. This design leads a new direction for sustainable, fluorine-free textile coatings. During the manufacturing process, the present invention finely controls the warp and weft density, line density, fabric density and thickness of polyester fibers to ensure that the fabric is both effectively waterproof and tough in a high-wear environment. High fiber density reduces water penetration and enhances wear resistance; appropriate line density balances strength and softness; high-density fabric structure improves overall strength and waterproof effect; moderate thickness takes into account both lightness and tear and wear resistance. These optimization measures jointly improve the comprehensive performance of polyester fabrics, meeting high-performance requirements while ensuring comfort and durability.

[0033] 2. The present invention uses dandelion-shaped alumina-modified composite rubber as a wear-resistant and anti-skid layer, and through chemical and physical modification, significantly improves the wear resistance, flexibility, waterproofness, anti-skid and mechanical properties of the gloves. Alumina nanoparticles enhance wear resistance, maleic anhydride grafting enhances flexibility and elasticity, dense structure and chemical stability enhance waterproofness, and the rough surface of nanoparticles and the high friction coefficient of rubber synergistically enhance anti-skid. The overall design maintains light weight while showing excellent comprehensive mechanical properties, providing an efficient, safe and comfortable solution for industrial protection. The present invention integrates multiple materials and technologies to innovate the design of wear-resistant and anti-skid bumps. By accurately proportioning high-performance ingredients such as natural latex, nitrile rubber latex, dumbbell-shaped nano-silicon carbide, etc., combined with point coating and vulcanization treatment, strong and wear-resistant bumps are made. The unique morphology of dumbbell-shaped nano-silicon carbide enhances the interface bonding force and improves the overall performance. The bump diameter is 1.0-2.0mm, the height is 0.5-1.5mm, and the distribution density is 10-25 / cm 2 , optimize anti-slip, wear resistance and comfort.

[0034] 3. The present invention innovatively designs wear-resistant and anti-skid convex points, integrating a variety of high-performance materials and advanced processes, including natural latex, nitrile rubber latex, etc., through dot coating and vulcanization treatment, to ensure the firm bonding of materials and performance optimization. Dumbbell-shaped nano silicon carbide particles are especially used to enhance the interface bonding force and improve the overall performance. The geometric parameters of the convex points are optimized to take into account anti-skid, wear resistance and comfort. This design significantly improves the waterproof, wear-resistant and anti-skid performance, providing efficient protection for the gloves.

[0035] 4. The highly wear-resistant and waterproof cycling heated gloves achieve waterproof and wear-resistant outer layer protection through the synergistic effect of multi-layer structure and materials, ensuring that the hands are kept dry and the service life of the gloves is extended in various weather conditions. The heat insulation layer works together with the strip-shaped heating layer to effectively keep warm and evenly distribute heat, ensuring that the hands remain warm in cold environments, thereby improving the comfort of riding. At the same time, the wear-resistant and shock-absorbing rubber pad on the palm and the wear-resistant and anti-skid layer on the front of the fingers enhance the anti-skid performance and shock absorption effect of the gloves, and improve the safety and comfort during riding. In addition, the battery bag and rechargeable battery design of the elastic waterproof fabric, combined with the switch and temperature control knob of the temperature control module, provide a convenient temperature adjustment function, increasing the flexibility and convenience of use. The layers are firmly connected by stitches and polyurethane adhesives, which enhances the integrity and durability of the glove structure and ensures that it is not easy to delaminate or damage during use. On the whole, this glove is suitable for use in bad weather and long-term riding under the synergistic effects of waterproof, wear-resistant, warm, shock-absorbing, and anti-skid, which significantly improves the comfort and safety of riders. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a front view of a highly wear-resistant and waterproof cycling heated glove proposed by the present invention.

[0037] Figure 2 This is a front view of the back of a highly wear-resistant and waterproof cycling heated glove proposed by the present invention.

[0038] Figure 3 for Figure 1 Cross-sectional view of the glove body at A.

[0039] Figure 4 The morphology of conventional stain droplets on the surface-modified polyester fabric of the waterproof and wear-resistant outer layer 11 prepared in Example 1 of the present invention.

[0040] Figure 5 The morphology of coffee stains on the surface-modified polyester fabric of the waterproof and wear-resistant outer layer 11 prepared in Comparative Example 1 of the present invention.

[0041] Figure 6 This is a morphology picture of the wear-resistant and anti-skid layer dandelion-shaped alumina prepared in Example 1 of the present invention.

[0042] Figure 7 This is the XRD phase analysis diagram of the dandelion-shaped alumina of the wear-resistant and anti-skid layer prepared in Example 1 of the present invention.

[0043] Figure 8 This is a morphology picture of dumbbell-shaped nano silicon carbide particles with wear-resistant and anti-slip convex points prepared in Example 1 of the present invention.

[0044] Fig. 9 This is an XRD phase analysis diagram of the dumbbell-shaped nano-silicon carbide particles with wear-resistant and anti-slip convex points prepared in Example 1 of the present invention.

[0045] Explanation of the accompanying drawings: 1. Glove body; 11. Waterproof and wear-resistant outer layer; 12. Heat insulation layer; 13. Heating layer; 14. Inner layer; 2. Battery bag; 3. Zipper; 4. Battery; 5. Temperature control module; 6. Wear-resistant and shock-absorbing rubber pad; 7. Wear-resistant and anti-slip bumps; 8. Wear-resistant and anti-slip layer. DETAILED DESCRIPTION

[0046] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0047] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0048] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0049]

[0050]

[0051] Example 1

[0052] See also Figure 1-3 A highly wear-resistant and waterproof cycling heated glove, comprising a glove body 1, wherein the glove body 1 is composed of a waterproof and wear-resistant outer layer 11, a heat-insulating layer 12, a heating layer 13 and an inner layer 14 from the outside to the inside; the waterproof and wear-resistant outer layer 11, the heat-insulating layer 12, the heating layer 13 and the inner layer 14 are connected together by stitches, and polyurethane adhesive is used to bond the layers; the heating layer 13 is distributed in the form of strips on the back of the hand of the glove body 1; a wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; a wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; a wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the front of the fingers of the glove body 1; the wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; the wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 ... The pad 6 and the wear-resistant and anti-skid layer 8 are both adhered to the surface of the glove body 1 by epoxy resin; the surface of the wear-resistant and shock-absorbing rubber pad 6 and the surface of the wear-resistant and anti-skid layer 8 are both provided with wear-resistant and anti-skid protrusions 7; a battery bag 2 is provided on the back of the hand on the back of the glove body 1; the battery bag 2 is made of elastic waterproof fabric; the battery bag 2 is provided with a zipper 3; the battery bag 2 has a built-in battery 4, and the battery 4 is a rechargeable battery 4; a temperature control module 5 is also provided on the back of the hand on the back of the glove body 1; the temperature control module 5 is provided with a switch and a temperature control knob; the battery 4 and the heating layer 13 are respectively connected to the temperature control module 5 through wires.

[0053] The waterproof and wear-resistant outer layer 11 is a surface-modified polyester fabric, which is prepared by an impregnation-compression-curing process. The polyester fabric is first completely immersed in a fluorine-free sol for 5 minutes, and then pressed between two rollers of an automatic filling machine at a compression pressure of 2 kg / cm 2 After the sheeting treatment, a curing treatment is performed. The curing treatment parameters are: drying at 75°C for 10 minutes, then putting it into a 125°C oven for curing for 5 minutes, and then repeating the impregnation-sheeting-curing process three times to finally obtain a surface-modified polyester fabric.

[0054] The preparation method of the fluorine-free sol of this embodiment is as follows: after uniformly mixing 10 parts of hexadecyltrimethoxysilane, 12 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 30 parts of ethanol by weight, 6 parts of hydrochloric acid and 4 parts of 1-methylimidazole are simultaneously added dropwise thereto, and then stirred at room temperature for 20 hours to finally obtain the fluorine-free sol.

[0055] The polyester fabric of this embodiment is woven from polyester fibers. The density of the polyester fiber warp and polyester fiber weft are 55 strands / cm and 70 strands / cm respectively. The weight of the polyester fiber is 4.5 g / km. The density of the polyester fabric is 60 g / m 2 , the thickness of the polyester fabric is 1mm.

[0056] The wear-resistant and anti-skid layer 8 is a dandelion-shaped alumina-modified composite rubber, and its preparation method is as follows: in parts by weight, 10 parts of natural rubber and 9 parts of EPDM rubber are added to a double-roll mill, heated to 30°C, crushed and softened for 8 minutes, and then 3 parts of surface-modified dandelion-shaped alumina nanoparticles, 2 parts of maleic anhydride-grafted EPDM rubber and 2 parts of stearic acid are added, heated to 45°C, mixed at 60rpm for 10 minutes, then 2 parts of sulfur are added, and mixing is continued for 5 minutes. Finally, the mixed colloid is taken out and made into sheets using a double-roll mill, and then it is vulcanized at 150°C and 25MPa for 5 minutes. After the vulcanization is completed, the vulcanized sheet is immediately taken out from the mold and quickly cooled under running water.

[0057] The preparation method of the surface modified dandelion-shaped aluminum oxide nanoparticles of this embodiment is as follows: by weight, 15 parts of sea urchin-shaped aluminum oxide nanoparticles are added to 80 parts of toluene and ultrasonically dispersed for 20 minutes, and then 3 parts of (3-aminopropyl) triethoxysilane are added and stirred at 75°C for 20 hours. After cooling, the filter is filtered and the filter residue is washed three times with toluene. The toluene needs to completely submerge the filter residue in each washing process. After washing, the filter residue is placed in a vacuum drying oven at room temperature and dried for 24 hours to obtain surface modified dandelion-shaped aluminum oxide nanoparticles.

[0058] The preparation method of dandelion-shaped alumina nanoparticles in this embodiment is as follows: in parts by weight, 6 parts of aluminum nitrate, 10 parts of ammonium sulfate and 100 parts of deionized water are mixed evenly, and then dripped dropwise into 200 parts of ammonium bicarbonate solution with a concentration of 1.5 mol / L. During the dripping process, it is necessary to stir evenly at a speed of 100 rpm, and then after standing for 10 hours, a precursor gel is obtained by filtering, and then the precursor gel is washed three times with deionized water, and each washing needs to completely submerge the precursor gel with deionized water. After washing, it is dried in an oven until complete, and then placed in a muffle furnace for calcination to obtain dandelion-shaped alumina nanoparticles, wherein the calcination process parameters are: in an air atmosphere, the calcination temperature is 1100°C, and the calcination time is 2 hours.

[0059] The preparation method of the wear-resistant and anti-skid convex points of the present embodiment is as follows: after uniformly mixing 3 parts of natural latex, 30 parts of nitrile rubber latex, 5 parts of dumbbell-shaped nano silicon carbide ceramic particles, 2 parts of EPDM elastomer powder, 1 part of silane coupling agent KH-550 and 2 parts of sulfur by weight, the mixture is applied on the wear-resistant and shock-absorbing rubber pad 6 and the wear-resistant and anti-skid layer 8 in a dot-like coating manner, and then vulcanization treatment is performed. The parameters of the vulcanization treatment are: first, heat preservation at 45°C for 30 minutes, then heat to 85°C for 30 minutes, and cool after the vulcanization is completed.

[0060] The preparation method of the dumbbell-shaped nano-silicon carbide particles of this embodiment is as follows: by weight, 20 parts of silicon dioxide, 20 parts of sucrose and 2 parts of ferrocene are mixed uniformly by high-energy ball milling to obtain a nano-scale precursor, which is then heated to 1200°C at a heating rate of 5°C / min in a tubular furnace in an argon atmosphere, kept warm for 2 hours, and cooled to obtain dumbbell-shaped nano-silicon carbide particles.

[0061] The dumbbell-shaped nano-silicon carbide particles of this embodiment have an average length of 100 nm and a diameter of 45 nm.

[0062] The wear-resistant and anti-skid convex points of this embodiment are spherical and evenly distributed on the wear-resistant and shock-absorbing rubber pad 6 and the wear-resistant and anti-skid layer 8. The diameter of the wear-resistant and anti-skid convex points is 1.0 mm; the height is 0.5 mm, and the distribution density is 10 / cm 2 .

[0063] The heat insulating layer 12 of this embodiment is 3M Thinsulate fx type thermal insulation material.

[0064] The heating layer 13 of this embodiment is a self-limiting temperature electric heating film.

[0065] The inner layer 14 of this embodiment is a Coolmax fiber knitted fabric.

[0066] Embodiment 2:

[0067] See also Figure 1-3A highly wear-resistant and waterproof cycling heated glove, comprising a glove body 1, wherein the glove body 1 is composed of a waterproof and wear-resistant outer layer 11, a heat-insulating layer 12, a heating layer 13 and an inner layer 14 from the outside to the inside; the waterproof and wear-resistant outer layer 11, the heat-insulating layer 12, the heating layer 13 and the inner layer 14 are connected together by stitches, and polyurethane adhesive is used to bond the layers; the heating layer 13 is distributed in the form of strips on the back of the hand of the glove body 1; a wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; a wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; a wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the front of the fingers of the glove body 1; the wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; the wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 ... The pad 6 and the wear-resistant and anti-skid layer 8 are both adhered to the surface of the glove body 1 by epoxy resin; the surface of the wear-resistant and shock-absorbing rubber pad 6 and the surface of the wear-resistant and anti-skid layer 8 are both provided with wear-resistant and anti-skid protrusions 7; a battery bag 2 is provided on the back of the hand on the back of the glove body 1; the battery bag 2 is made of elastic waterproof fabric; the battery bag 2 is provided with a zipper 3; the battery bag 2 has a built-in battery 4, and the battery 4 is a rechargeable battery 4; a temperature control module 5 is also provided on the back of the hand on the back of the glove body 1; the temperature control module 5 is provided with a switch and a temperature control knob; the battery 4 and the heating layer 13 are respectively connected to the temperature control module 5 through wires.

[0068] The waterproof and wear-resistant outer layer 11 is a surface-modified polyester fabric, which is prepared by an impregnation-compression-curing process. The polyester fabric is first completely immersed in a fluorine-free sol for 6 minutes, and then pressed between two rollers of an automatic filling machine at a compression pressure of 2.4 kg / cm 2 After the sheeting treatment, the curing treatment is carried out. The curing treatment parameters are: drying at 79°C for 14 minutes, then putting it into a 130°C oven for curing for 7 minutes, and then repeating the impregnation-sheeting-curing process three times to finally obtain a surface-modified polyester fabric.

[0069] The preparation method of the fluorine-free sol of this embodiment is as follows: after uniformly mixing 13 parts of hexadecyltrimethoxysilane, 15 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 37 parts of ethanol by weight, 8 parts of hydrochloric acid and 5 parts of 1-methylimidazole are simultaneously added dropwise thereto, and then stirred at room temperature for 23 hours to finally obtain the fluorine-free sol.

[0070] The polyester fabric of this embodiment is woven from polyester fibers. The densities of the polyester fiber warp and polyester fiber weft are 59 strands / cm and 77 strands / cm respectively. The weight of the polyester fiber is 4.9 g / km. The density of the polyester fabric is 63 g / m 2 , the thickness of the polyester fabric is 1.3mm.

[0071] The wear-resistant and anti-skid layer 8 is a dandelion-shaped alumina-modified composite rubber, and its preparation method is as follows: in parts by weight, 12 parts of natural rubber and 14 parts of EPDM rubber are added to a double-roll mill, heated to 33°C, crushed and softened for 11 minutes, and then 5 parts of surface-modified dandelion-shaped alumina nanoparticles, 3 parts of maleic anhydride-grafted EPDM rubber and 3 parts of stearic acid are added, heated to 50°C, mixed at 70rpm for 14 minutes, then 4 parts of sulfur are added, and mixing is continued for 7 minutes. Finally, the mixed colloid is taken out and made into sheets using a double-roll mill, and then it is vulcanized at 158°C and 30MPa for 7 minutes. After the vulcanization is completed, the vulcanized sheet is immediately taken out from the mold and quickly cooled under running water.

[0072] The preparation method of the surface modified dandelion-shaped aluminum oxide nanoparticles of this embodiment is as follows: by weight, 20 parts of sea urchin-shaped aluminum oxide nanoparticles are added to 90 parts of toluene and ultrasonically dispersed for 32 minutes, and then 5 parts of (3-aminopropyl) triethoxysilane are added and stirred at 80°C for 27 hours. After cooling, the filter is filtered and the filter residue is washed three times with toluene. The toluene needs to completely submerge the filter residue in each washing process. After washing, the filter residue is placed in a vacuum drying oven at room temperature and dried for 30 hours to obtain surface modified dandelion-shaped aluminum oxide nanoparticles.

[0073] The preparation method of dandelion-shaped alumina nanoparticles in this embodiment is as follows: in parts by weight, 10 parts of aluminum nitrate, 14 parts of ammonium sulfate and 100 parts of deionized water are mixed evenly, and then dripped dropwise into 200 parts of ammonium bicarbonate solution with a concentration of 1.5 mol / L. During the dripping process, it is necessary to stir evenly at a speed of 130 rpm, and then after standing for 15 hours, a precursor gel is obtained by filtering, and then the precursor gel is washed three times with deionized water, and each washing needs to completely submerge the precursor gel with deionized water. After washing, it is dried in an oven until complete, and then placed in a muffle furnace for calcination to obtain dandelion-shaped alumina nanoparticles, wherein the calcination process parameters are: in an air atmosphere, the calcination temperature is 1180°C, and the calcination time is 3 hours.

[0074] The preparation method of the wear-resistant and anti-skid convex points of the present embodiment is as follows: after mixing evenly by weight, 5 parts of natural latex, 38 parts of nitrile rubber latex, 6 parts of dumbbell-shaped nano silicon carbide ceramic particles, 4 parts of EPDM elastomer powder, 2 parts of silane coupling agent KH-550 and 3 parts of sulfur, apply the mixture on the wear-resistant shock-absorbing rubber pad 6 and the wear-resistant and anti-skid layer 8 in a dot-like coating manner, and then perform vulcanization treatment. The parameters of the vulcanization treatment are: first keep warm at 52°C for 35 minutes, then heat to 92°C for 38 minutes, and cool after the vulcanization is completed.

[0075] The preparation method of the dumbbell-shaped nano-silicon carbide particles of this embodiment is as follows: by weight, 27 parts of silicon dioxide, 25 parts of sucrose and 4 parts of ferrocene are mixed uniformly by high-energy ball milling to obtain a nano-scale precursor, which is then heated to 1300°C at a heating rate of 7.5°C / min in a tubular furnace in an argon atmosphere, kept warm for 3 hours, and cooled to obtain dumbbell-shaped nano-silicon carbide particles.

[0076] The dumbbell-shaped nano-silicon carbide particles of this embodiment have an average length of 133 nm and a diameter of 65 nm.

[0077] The wear-resistant and anti-skid convex points of this embodiment are spherical and evenly distributed on the wear-resistant and shock-absorbing rubber pad 6 and the wear-resistant and anti-skid layer 8. The diameter of the wear-resistant and anti-skid convex points is 1.3 mm; the height is 1 mm, and the distribution density is 15 / cm 2 .

[0078] The heat insulating layer 12 of this embodiment is 3M Thinsulate fx type thermal insulation material.

[0079] The heating layer 13 of this embodiment is a self-limiting temperature electric heating film.

[0080] The inner layer 14 of this embodiment is a Coolmax fiber knitted fabric.

[0081] Example 3

[0082] See also Figure 1-3 A highly wear-resistant and waterproof cycling heated glove, comprising a glove body 1, wherein the glove body 1 is composed of a waterproof and wear-resistant outer layer 11, a heat-insulating layer 12, a heating layer 13 and an inner layer 14 from the outside to the inside; the waterproof and wear-resistant outer layer 11, the heat-insulating layer 12, the heating layer 13 and the inner layer 14 are connected together by stitches, and polyurethane adhesive is used to bond the layers; the heating layer 13 is distributed in the form of strips on the back of the hand of the glove body 1; a wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; a wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; a wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the front of the fingers of the glove body 1; the wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; the wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 ... The pad 6 and the wear-resistant and anti-skid layer 8 are both adhered to the surface of the glove body 1 by epoxy resin; the surface of the wear-resistant and shock-absorbing rubber pad 6 and the surface of the wear-resistant and anti-skid layer 8 are both provided with wear-resistant and anti-skid protrusions 7; a battery bag 2 is provided on the back of the hand on the back of the glove body 1; the battery bag 2 is made of elastic waterproof fabric; the battery bag 2 is provided with a zipper 3; the battery bag 2 has a built-in battery 4, and the battery 4 is a rechargeable battery 4; a temperature control module 5 is also provided on the back of the hand on the back of the glove body 1; the temperature control module 5 is provided with a switch and a temperature control knob; the battery 4 and the heating layer 13 are respectively connected to the temperature control module 5 through wires.

[0083] The waterproof and wear-resistant outer layer 11 is a surface-modified polyester fabric, which is prepared by an impregnation-compression-curing process. The polyester fabric is first completely immersed in a fluorine-free sol for 8 minutes, and then pressed between two rollers of an automatic filling machine at a compression pressure of 3 kg / cm 2 After the sheeting treatment, the curing treatment is carried out. The curing treatment parameters are: drying at 80°C for 14 minutes, then putting it into a 130°C oven for curing for 8 minutes, and then repeating the impregnation-sheeting-curing process three times to finally obtain a surface-modified polyester fabric.

[0084] The preparation method of the fluorine-free sol of this embodiment is as follows: after uniformly mixing 16 parts of hexadecyltrimethoxysilane, 17 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 42 parts of ethanol by weight, 10 parts of hydrochloric acid and 6 parts of 1-methylimidazole are simultaneously added dropwise thereto, and then stirred at room temperature for 26 hours to finally obtain the fluorine-free sol.

[0085] The polyester fabric of this embodiment is woven from polyester fibers. The densities of the polyester fiber warp and polyester fiber weft are 61 strands / cm and 79 strands / cm respectively. The weight of the polyester fiber is 5.1 g / km. The density of the polyester fabric is 65 g / m 2 , the thickness of the polyester fabric is 1.6mm.

[0086] The wear-resistant and anti-skid layer 8 is a dandelion-shaped alumina-modified composite rubber, and its preparation method is as follows: 13 parts of natural rubber and 14 parts of EPDM rubber are added to a double-roll mill by weight, heated to 36°C, crushed and softened for 13 minutes, and then 6 parts of surface-modified dandelion-shaped alumina nanoparticles, 4 parts of maleic anhydride-grafted EPDM rubber and 3 parts of stearic acid are added, heated to 51°C, mixed at 72rpm for 14 minutes, then 5 parts of sulfur are added, and mixing is continued for 8 minutes. Finally, the mixed colloid is taken out and made into sheets using a double-roll mill, and then it is vulcanized at 158°C and 31MPa for 7 minutes. After the vulcanization is completed, the vulcanized sheet is immediately taken out from the mold and quickly cooled under running water.

[0087] The preparation method of the surface modified dandelion-shaped aluminum oxide nanoparticles of this embodiment is as follows: by weight, 21 parts of sea urchin-shaped aluminum oxide nanoparticles are added to 92 parts of toluene and ultrasonically dispersed for 34 minutes, and then 5 parts of (3-aminopropyl) triethoxysilane are added and stirred at 80°C for 29 hours. After cooling, the filter is filtered and the filter residue is washed three times with toluene. The toluene needs to completely submerge the filter residue in each washing process. After washing, the filter residue is placed in a vacuum drying oven at room temperature and dried for 31 hours to obtain surface modified dandelion-shaped aluminum oxide nanoparticles.

[0088] The preparation method of dandelion-shaped alumina nanoparticles in this embodiment is as follows: in parts by weight, 12 parts of aluminum nitrate, 14 parts of ammonium sulfate and 100 parts of deionized water are mixed evenly, and then dripped dropwise into 200 parts of ammonium bicarbonate solution with a concentration of 1.5 mol / L. During the dripping process, it is necessary to stir evenly at a speed of 130 rpm, and then after standing for 16 hours, a precursor gel is obtained by filtering, and then the precursor gel is washed three times with deionized water, and each washing needs to completely submerge the precursor gel with deionized water. After washing, it is dried in an oven until complete, and then placed in a muffle furnace for calcination to obtain dandelion-shaped alumina nanoparticles, wherein the calcination process parameters are: in an air atmosphere, the calcination temperature is 1220°C, and the calcination time is 3 hours.

[0089] The preparation method of the wear-resistant and anti-skid bumps of the present embodiment is as follows: after uniformly mixing 7 parts of natural latex, 42 parts of nitrile rubber latex, 7 parts of dumbbell-shaped nano silicon carbide ceramic particles, 5 parts of EPDM elastomer powder, 2 parts of silane coupling agent KH-550 and 3 parts of sulfur by weight, the mixture is applied on the wear-resistant and shock-absorbing rubber pad 6 and the wear-resistant and anti-skid layer 8 in a dot-like manner, and then vulcanization treatment is performed. The parameters of the vulcanization treatment are: first, heat preservation at 55°C for 38 minutes, then heat to 94°C for 40 minutes, and cool after the vulcanization is completed.

[0090] The preparation method of the dumbbell-shaped nano-silicon carbide particles of this embodiment is as follows: by weight, 30 parts of silicon dioxide, 27 parts of sucrose and 4 parts of ferrocene are mixed uniformly by high-energy ball milling to obtain a nano-scale precursor, which is then heated to 1350° C. at a heating rate of 8° C. / min in a tubular furnace in an argon atmosphere, kept warm for 3 hours, and cooled to obtain dumbbell-shaped nano-silicon carbide particles.

[0091] The dumbbell-shaped nano-silicon carbide particles of this embodiment have an average length of 160 nm and a diameter of 75 nm.

[0092] The wear-resistant and anti-skid convex points of this embodiment are spherical and evenly distributed on the wear-resistant and shock-absorbing rubber pad 6 and the wear-resistant and anti-skid layer 8. The diameter of the wear-resistant and anti-skid convex points is 1.5 mm, the height is 1.2 mm, and the distribution density is 22 / cm 2 .

[0093] The heat insulating layer 12 of this embodiment is 3M Thinsulate fx type thermal insulation material.

[0094] The heating layer 13 of this embodiment is a self-limiting temperature electric heating film.

[0095] The inner layer 14 of this embodiment is a Coolmax fiber knitted fabric.

[0096] Example 4

[0097] See also Figure 1-3 A highly wear-resistant and waterproof cycling heated glove, comprising a glove body 1, wherein the glove body 1 is composed of a waterproof and wear-resistant outer layer 11, a heat-insulating layer 12, a heating layer 13 and an inner layer 14 from the outside to the inside; the waterproof and wear-resistant outer layer 11, the heat-insulating layer 12, the heating layer 13 and the inner layer 14 are connected together by stitches, and polyurethane adhesive is used to bond the layers; the heating layer 13 is distributed in the form of strips on the back of the hand of the glove body 1; a wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; a wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; a wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the front of the fingers of the glove body 1; the wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 is provided on the palm of the glove body 1; the wear-resistant and anti-skid layer 8 is provided on the front of the fingers of the glove body 1; the wear-resistant and shock-absorbing rubber pad 6 ... The pad 6 and the wear-resistant and anti-skid layer 8 are both adhered to the surface of the glove body 1 by epoxy resin; the surface of the wear-resistant and shock-absorbing rubber pad 6 and the surface of the wear-resistant and anti-skid layer 8 are both provided with wear-resistant and anti-skid protrusions 7; a battery bag 2 is provided on the back of the hand on the back of the glove body 1; the battery bag 2 is made of elastic waterproof fabric; the battery bag 2 is provided with a zipper 3; the battery bag 2 has a built-in battery 4, and the battery 4 is a rechargeable battery 4; a temperature control module 5 is also provided on the back of the hand on the back of the glove body 1; the temperature control module 5 is provided with a switch and a temperature control knob; the battery 4 and the heating layer 13 are respectively connected to the temperature control module 5 through wires.

[0098] The waterproof and wear-resistant outer layer 11 is a surface-modified polyester fabric, which is prepared by an impregnation-compression-curing process. The polyester fabric is first completely immersed in a fluorine-free sol for 10 minutes, and then pressed between two rollers of an automatic filling machine at a compression pressure of 3 kg / cm 2 After the sheeting treatment, a curing treatment is performed. The curing treatment parameters are: drying at 85°C for 20 minutes, then putting it into a 135°C oven for curing for 10 minutes, and then repeating the impregnation-sheeting-curing process three times to finally obtain a surface-modified polyester fabric.

[0099] The preparation method of the fluorine-free sol of this embodiment is as follows: after uniformly mixing 18 parts of hexadecyltrimethoxysilane, 20 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 50 parts of ethanol by weight, 12 parts of hydrochloric acid and 8 parts of 1-methylimidazole are simultaneously added dropwise thereto, and then stirred at room temperature for 30 hours to finally obtain the fluorine-free sol.

[0100] The polyester fabric of this embodiment is woven from polyester fibers. The densities of the polyester fiber warp and polyester fiber weft are 65 strands / cm and 85 strands / cm respectively. The weight of the polyester fiber is 5.5 g / km. The density of the polyester fabric is 68 g / m 2 , the thickness of the polyester fabric is 2mm.

[0101] The wear-resistant and anti-skid layer 8 is a dandelion-shaped alumina-modified composite rubber, and its preparation method is as follows: by weight, 16 parts of natural rubber and 18 parts of EPDM rubber are added to a double-roll mill, heated to 40°C, crushed and softened for 16 minutes, and then 8 parts of surface-modified dandelion-shaped alumina nanoparticles, 5 parts of maleic anhydride-grafted EPDM rubber and 4 parts of stearic acid are added, heated to 55°C, mixed at 80rpm for 18 minutes, then 6 parts of sulfur are added, and mixing is continued for 10 minutes. Finally, the mixed colloid is taken out and made into sheets using a double-roll mill, and then it is vulcanized at 165°C and 35MPa for 9 minutes. After the vulcanization is completed, the vulcanized sheet is immediately taken out from the mold and quickly cooled under running water.

[0102] The preparation method of the surface modified dandelion-shaped aluminum oxide nanoparticles of this embodiment is as follows: by weight, 25 parts of sea urchin-shaped aluminum oxide nanoparticles are added to 100 parts of toluene and ultrasonically dispersed for 45 minutes, and then 7 parts of (3-aminopropyl) triethoxysilane are added and stirred for reaction at 85°C for 35 hours. After cooling, the filter is filtered and the filter residue is washed three times with toluene. The toluene needs to completely submerge the filter residue in each washing process. After washing, the filter residue is placed in a vacuum drying oven at room temperature and dried for 36 hours to obtain surface modified dandelion-shaped aluminum oxide nanoparticles.

[0103] The preparation method of dandelion-shaped alumina nanoparticles in this embodiment is as follows: in parts by weight, 15 parts of aluminum nitrate, 18 parts of ammonium sulfate and 100 parts of deionized water are mixed evenly, and then dripped dropwise into 200 parts of ammonium bicarbonate solution with a concentration of 1.5 mol / L. During the dripping process, it is necessary to stir evenly at a speed of 160 rpm, and then after standing for 20 hours, a precursor gel is obtained by filtering, and then the precursor gel is washed three times with deionized water, and each washing needs to completely submerge the precursor gel with deionized water. After washing, it is dried in an oven until complete, and then placed in a muffle furnace for calcination to obtain dandelion-shaped alumina nanoparticles, wherein the calcination process parameters are: in an air atmosphere, the calcination temperature is 1250°C, and the calcination time is 4 hours.

[0104] The preparation method of the wear-resistant and anti-skid protrusions 7 of the present embodiment is as follows: 8 parts of natural latex, 45 parts of nitrile rubber latex, 8 parts of dumbbell-shaped nano silicon carbide ceramic particles, 6 parts of EPDM elastomer powder, 3 parts of silane coupling agent KH-550 and 4 parts of sulfur are mixed evenly by weight, and then coated on the wear-resistant shock-absorbing rubber pad 6 and the wear-resistant and anti-skid layer 8 in a dot-coating manner, and then vulcanization treatment is performed. The parameters of the vulcanization treatment are: first, keep warm at 60°C for 40 minutes, then heat to 100°C and keep warm for 45 minutes, and cool after the vulcanization is completed.

[0105] The preparation method of the dumbbell-shaped nano-silicon carbide particles of this embodiment is as follows: by weight, 35 parts of silicon dioxide, 30 parts of sucrose and 5 parts of ferrocene are mixed uniformly by high-energy ball milling to obtain a nano-scale precursor, which is then heated to 1400°C at a heating rate of 10°C / min in a tubular furnace in an argon atmosphere, kept warm for 4 hours, and cooled to obtain dumbbell-shaped nano-silicon carbide particles.

[0106] The dumbbell-shaped nano-silicon carbide particles of this embodiment have an average length of 200 nm and a diameter of 85 nm.

[0107] The wear-resistant and anti-skid convex points 7 of this embodiment are spherical and evenly distributed on the wear-resistant and shock-absorbing rubber pad 6 and the wear-resistant and anti-skid layer 8. The diameter of the wear-resistant and anti-skid convex points 7 is 2.0 mm; the height is 1.5 mm, and the distribution density is 25 / cm 2 The heat insulation layer 12 of this embodiment is 3M Thinsulate fx type thermal insulation material.

[0108] The heating layer 13 of this embodiment is a self-limiting temperature electric heating film.

[0109] The inner layer 14 of this embodiment is a Coolmax fiber knitted fabric.

[0110] Example 5

[0111] It is basically the same as Example 1, except that the surface-modified dandelion-shaped aluminum oxide nanoparticles used to prepare the wear-resistant and anti-skid layer 8 are 8 parts.

[0112] Comparative Example 1

[0113] It is basically the same as Example 1, except that the waterproof and wear-resistant outer layer 11 is a polyester fabric that has not been surface-modified.

[0114] Comparative Example 2

[0115] It is basically the same as Example 1, except that the wear-resistant and anti-skid layer 8 is prepared using traditional granular aluminum oxide particles instead of dandelion-shaped aluminum oxide particles.

[0116] Comparative Example 3

[0117] It is basically the same as Example 1, except that the wear-resistant and anti-skid protrusions 7 are made of traditional granular silicon carbide particles instead of dumbbell-shaped silicon carbide particles.

[0118] Characterization Tests:

[0119] Figure 4The morphology of conventional droplets (such as water droplets, coffee, tea and milk) on the surface-modified polyester fabric of the waterproof and wear-resistant outer layer 11 prepared in Example 1 of the present invention is shown. These droplets show hydrophobic characteristics similar to lotus leaf dew on the surface of the material. This means that when these liquids come into contact with the surface of the material, they do not penetrate or diffuse rapidly, but form relatively complete spherical or hemispherical droplets, maintaining their original shape. This phenomenon is a direct manifestation of waterproof performance, because it shows that the material has good repellency to a variety of common liquids, thereby achieving a waterproof effect. In contrast, Figure 5 The figure shows the morphology of coffee stains on the waterproof and wear-resistant outer layer 11 prepared in Comparative Example 1 of the present invention. It can be seen from the figure that the coffee substance has obviously penetrated into the waterproof and wear-resistant outer layer, rather than Figure 4 This phenomenon directly proves that the comparative material has no or poor waterproof performance, because liquid can easily penetrate its surface and leave stains. Figure 4 and Figure 5 We can clearly see the significant advantage of the waterproof and wear-resistant outer layer 11 prepared in Example 1 of the present invention in terms of waterproof performance. The material can effectively repel a variety of common liquids, prevent them from penetrating and leaving stains, and thus show higher practical value and performance stability in actual applications.

[0120] Observation by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) Figure 6 and Figure 8 The morphology shown in the figure and X-ray diffraction (XRD) analysis Figure 7 and Fig. 9 According to the phase analysis shown in , we have conducted a detailed verification of the dandelion-shaped alumina of the wear-resistant and anti-skid layer and the dumbbell-shaped nano-silicon carbide particles with wear-resistant and anti-skid bumps prepared in Example 1 of the present invention. The morphology analysis results show that the dandelion-shaped alumina has a uniform nanostructure, showing typical dandelion-shaped features; the dumbbell-shaped nano-silicon carbide particles have uniform length and diameter, reflecting an ideal dumbbell-shaped structure, indicating that the prepared material has good morphological consistency and structural integrity at the nanoscale. The phase analysis results show that the XRD spectrum of the dandelion-shaped alumina shows that it is a characteristic peak of α-phase alumina, and the XRD spectrum of the dumbbell-shaped nano-silicon carbide particles shows that it is a characteristic peak of β-phase silicon carbide. The positions and intensities of these diffraction peaks are in good agreement with the standard data, further verifying the purity and crystal structure of the material. In summary, the SEM, TEM and XRD analysis results show that the dandelion-shaped alumina and dumbbell-shaped nano-silicon carbide particles prepared in Example 1 of the present invention have met the expected design requirements in terms of morphology and crystal structure, verifying the rationality and effectiveness of the adopted preparation process. The excellent properties of these materials provide a solid foundation for their application in wear-resistant and anti-skid layers.

[0121] Performance Test:

[0122] Waterproofness test: Use contact angle meter (DSA100, The water contact angle (WCA) of the membrane was measured by using AATCC (AATCC GmbH, Hamburg, Germany). According to AATCC test method 127-2003, a hydrostatic pressure tester (YG825E, Nantong Hongda Experimental Instrument Co., Ltd., Nantong, China) was used to measure the waterproof properties of the membrane under hydrostatic pressure (ΔP), and the water contact angle before and after abrasion was tested.

[0123] Abrasion test: refer to DIN EN ISO 12947-4-2007 "Textiles - Determination of the abrasion resistance of fabrics by the Martindale method - Part 4: Evaluation of changes in appearance". During the test, select 3 samples with a diameter of (38.0±0.5) mm. If the sample weight is less than 500g / m2 or the sample is a single-layer fabric, a foam pad with a diameter of (38.0±0.5) mm is required under the sample. Wool standard fabric and felt are used as abrasives with a diameter of (140.0±0.5) mm. Subsequently, the sample is placed on the Martindale abrasion tester for 35,000 abrasion tests. The criteria for judging whether the abrasion test is qualified are: no pilling, broken yarn, severe pilling or rough surface on the surface of the fabric, and the center of the velvet is not smooth and whitened; otherwise, it is unqualified.

[0124] The waterproof properties of the surface-modified polyester fabrics of the waterproof and wear-resistant outer layers of Examples 1 to 5 and Comparative Example 1 are summarized in Table 2.

[0125] The wear resistance of the waterproof and wear-resistant outer layer, the wear-resistant and anti-skid layer, the wear-resistant and shock-absorbing rubber pad with wear-resistant and anti-skid convex points on the surface, and the wear-resistant and anti-skid layer with wear-resistant and anti-skid convex points on the surface of Examples 1 to 5 and Comparative Examples 1 to 3 are summarized in Table 3.

[0126] Table 2 Performance of surface modified polyester fabrics of Examples 1 to 5 and Comparative Example 1

[0127]

[0128]

[0129] Table 3 Wear resistance of the wear-resistant and anti-skid convex points on the surface of the wear-resistant and anti-skid layer and the wear-resistant and shock-absorbing rubber pad in Examples 1 to 5

[0130]

[0131] The main difference between Comparative Example 1 and Example 1 is whether the waterproof and wear-resistant outer polyester fabric is surface-modified. From Tables 2 and 3, it can be seen that the surface-modified polyester fabric can significantly improve its wear resistance and waterproofness.

[0132] The main difference between Comparative Example 2 and Example 1 is whether the wear-resistant and anti-skid layer uses traditional granular aluminum oxide particles or dandelion-shaped aluminum oxide particles. As can be seen from Table 3, the wear-resistant and anti-skid layer prepared using dandelion-shaped aluminum oxide particles can significantly improve its wear resistance.

[0133] The main difference between Example 3 and Example 1 is whether the wear-resistant and anti-skid convex points are traditional granular silicon carbide particles or dumbbell-shaped silicon carbide particles. As can be seen from Table 3, the wear-resistant and anti-skid convex points prepared by dumbbell-shaped silicon carbide particles can significantly improve their wear resistance. Although the wear-resistant and anti-skid layer of Comparative Example 2 uses ordinary aluminum oxide particles, it still has excellent wear resistance due to the presence of wear-resistant and anti-skid convex points on its surface, which also proves that the wear-resistant and anti-skid convex points prepared by dumbbell-shaped silicon carbide particles can significantly improve their wear resistance.

[0134] In summary, the electric heating gloves of the present invention achieve waterproof, wear-resistant and self-cleaning properties by treating the outer layer of the polyester fabric with fluorine-free sol, and are combined with the dandelion-shaped alumina-modified composite rubber wear-resistant and anti-skid layer and the wear-resistant and anti-skid convex point design to comprehensively improve the waterproof, wear-resistant, anti-skid and comprehensive properties of the gloves.

[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A highly wear-resistant and waterproof cycling heated glove, characterized in that: The glove body (1) comprises a waterproof and wear-resistant outer layer (11), a heat-insulating layer (12), a heating layer (13) and an inner layer (14) from the outside to the inside; the waterproof and wear-resistant outer layer (11), the heat-insulating layer (12), the heating layer (13) and the inner layer (14) are connected together by stitches, and polyurethane adhesive is used to bond the layers; the heating layer (13) is distributed in the form of strips on the back of the hand of the glove body (1); a wear-resistant and shock-absorbing rubber pad (6) is provided on the palm of the glove body (1); a wear-resistant and anti-slip layer (8) is provided on the front of the fingers of the glove body (1); the wear-resistant and shock-absorbing rubber pad (6) and the wear-resistant and anti-slip layer ( 8) are both adhered to the surface of the glove body (1) by epoxy resin; the surface of the wear-resistant shock-absorbing rubber pad (6) and the surface of the wear-resistant anti-skid layer (8) are both provided with wear-resistant anti-skid protrusions (7); a battery bag (2) is provided on the back of the hand of the back of the glove body (1); the battery bag (2) is made of elastic waterproof fabric; the battery bag (2) is provided with a zipper; the battery bag (2) has a built-in storage battery (4), and the storage battery (4) is a rechargeable storage battery (4); a temperature control module (5) is also provided on the back of the hand of the back of the glove body (1); the temperature control module (5) is provided with a switch and a temperature control knob; the storage battery (4) and the heating layer (13) are respectively connected to the temperature control module (5) through wires; The waterproof and wear-resistant outer layer (11) is a surface-modified polyester fabric, and its preparation method is: an immersion-compression-curing process, firstly the polyester fabric is completely immersed in a fluorine-free sol, the immersion time is 5-10 minutes, and then the polyester fabric is pressed between two rollers of an automatic filling machine, and the pressing pressure is 2-3 kg / cm 2 After the sheeting treatment, the curing treatment is carried out. The curing treatment parameters are: drying at 75-85°C for 10-20 minutes, then curing in an oven at 125-135°C for 5-10 minutes, and then repeating the impregnation-sheeting-curing process three times to finally obtain a surface-modified polyester fabric; The wear-resistant and anti-skid layer (8) is a dandelion-shaped alumina-modified composite rubber, and its preparation method is as follows: by weight, 10-16 parts of natural rubber and 9-18 parts of EPDM rubber are added to a double-roll mill, heated to 30-40°C, crushed and softened for 8-16 minutes, then 3-8 parts of surface-modified dandelion-shaped alumina nanoparticles, 2-5 parts of maleic anhydride-grafted EPDM rubber and 2-4 parts of stearic acid are added, heated to 45-55°C, mixed at 60-80 rpm for 10-18 minutes, then 2-6 parts of sulfur are added, and mixing is continued for 5-10 minutes. Finally, the mixed colloid is taken out and formed into a sheet using a double-roll mill, and then it is vulcanized at 150-165°C and 25-35 MPa for 5-9 minutes. After the vulcanization is completed, the vulcanized sheet is immediately taken out from the mold and quickly cooled under running water. The preparation method of the fluorine-free sol is as follows: after 10 to 18 parts of hexadecyltrimethoxysilane, 12 to 20 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 30 to 50 parts of ethanol are uniformly mixed by weight, 6 to 12 parts of hydrochloric acid and 4 to 8 parts of 1-methylimidazole are simultaneously dripped therein in a dropwise manner, and then stirred at room temperature for 20 to 30 hours to finally obtain the fluorine-free sol; The preparation method of surface-modified dandelion-shaped aluminum oxide nanoparticles is as follows: by weight, 15 to 25 parts of dandelion-shaped aluminum oxide nanoparticles are added to 80 to 100 parts of toluene for ultrasonic dispersion for 20 to 45 minutes, and then 3 to 7 parts of (3-aminopropyl) triethoxysilane are added for stirring and reacting at 75 to 85° C. for 20 to 35 hours, and after cooling, the filter residue is filtered and washed three times with toluene, and the toluene needs to completely submerge the filter residue in each washing process. After washing, the filter residue is placed in a vacuum drying oven at room temperature and dried for 24 to 36 hours to obtain surface-modified dandelion-shaped aluminum oxide nanoparticles; The preparation method of dandelion-shaped alumina nanoparticles is as follows: in parts by weight, 6 to 15 parts of aluminum nitrate, 10 to 18 parts of ammonium sulfate and 100 parts of deionized water are mixed evenly, and then dripped dropwise into 200 parts of ammonium bicarbonate solution with a concentration of 1.5 mol / L. During the dripping process, it is necessary to stir evenly at a speed of 100 to 160 rpm, and then after standing for 10 to 20 hours, a precursor gel is obtained by filtering, and then the precursor gel is washed three times with deionized water. Each washing requires that the precursor gel is completely submerged with deionized water. After washing, it is dried in an oven until complete, and then placed in a muffle furnace for calcination to obtain dandelion-shaped alumina nanoparticles, wherein the calcination process parameters are: in an air atmosphere, the calcination temperature is 1100 to 1250°C, and the calcination time is 2 to 4 hours.

2. A highly wear-resistant and waterproof cycling heated glove as claimed in claim 1, characterized in that: The polyester fabric is woven from polyester fibers, the densities of the polyester fiber warp and polyester fiber weft are 55-65 strands / cm and 70-85 strands / cm respectively, the weight of the polyester fiber is 4.5-5.5 g / km, and the density of the polyester fabric is 60-68 g / m 2 , the thickness of polyester fabric is 1~2mm.

3. The highly wear-resistant and waterproof cycling heated gloves according to claim 1, characterized in that: The preparation method of the wear-resistant and anti-skid convex dots (7) is as follows: 3-8 parts of natural latex, 30-45 parts of nitrile rubber latex, 5-8 parts of dumbbell-shaped nano silicon carbide ceramic particles, 2-6 parts of EPDM elastomer powder, 1-3 parts of silane coupling agent KH-550 and 2-4 parts of sulfur are mixed evenly by weight, and then coated on the wear-resistant and anti-skid layer (8) in a dot coating manner, and then vulcanization treatment is performed. The parameters of the vulcanization treatment are: first, heat preservation at 45-60°C for 30-40 minutes, then heat to 85-100°C for 30-45 minutes, and cool after the vulcanization is completed; The preparation method of the dumbbell-shaped nano silicon carbide ceramic particles is as follows: by weight, 20 to 35 parts of silicon dioxide, 20 to 30 parts of sucrose and 2 to 5 parts of ferrocene are uniformly mixed by high-energy ball milling to obtain a nano-scale precursor, and then the precursor is heated to 1200 to 1400° C. at a heating rate of 5 to 10° C. / min in a tubular furnace in an argon atmosphere, kept warm for 2 to 4 hours, and cooled to obtain dumbbell-shaped nano silicon carbide ceramic particles.

4. A highly wear-resistant and waterproof cycling heated glove as claimed in claim 3, characterized in that: The dumbbell-shaped nano silicon carbide ceramic particles have an average length of 100-200 nm and a diameter of 45-85 nm.

5. A highly wear-resistant and waterproof cycling heated glove as claimed in claim 1 or 3, characterized in that: The wear-resistant and anti-skid convex points (7) are spherical and evenly distributed on the surface of the wear-resistant and anti-skid rubber pad (6) and the wear-resistant and anti-skid layer (8). The diameter of the wear-resistant and anti-skid convex points (7) is 1.0-2.0 mm; the height is 0.5-1.5 mm, and the distribution density is 10-25 / cm².

6. The highly wear-resistant and waterproof cycling heated gloves according to claim 1, characterized in that: The heat insulation layer (12) is 3M Thinsulate fx type thermal insulation material; The heating layer (13) is a self-limiting temperature electric heating film; The inner layer (14) is a Coolmax fiber knitted fabric.

Citation Information

Patent Citations

  • Aerogel electric heating glove

    CN212212820U

  • Skiing glove with heating function

    CN216909127U

  • Nano rubber patch composite sole

    CN104448424A

  • High-hardness wear-resisting cable sheathing material and preparation method thereof

    CN109054138A